Cartilage restoration : practical clinical applications - Gomoll, Andreas H.; Farr, Jack (Springer New York, 2014)
Attempting to bridge the gap between the science and art of cartilage restoration, Cartilage Restoration: Practical Clinical Applications combines an overview of clinical research and methodologies with clinical cases to help guide the orthopedic treatment and care of patients presenting with cartilage issues. With chapters written by internationally-renowned orthopedic surgeons, topics include an overview of current surgical options, debridement and marrow stimulation, autograft plug transfer, allografts, cell therapy, and meniscal issues. Cartilage Restoration is a valuable resource for orthopedic surgeons, residents, and fellows.